Implementing a Food Labeling and Marketing Law in Chile - Pizarro-Quevedo, T; Villalobos-Dintrans, P (Taylor and Francis Inc., 2020)
In 2012, Chile passed a law intended to reduce obesity in the country. It included several novel features, such as a front-of-package label, limitations to marketing and advertising, and policies targeting schools. The law required the creation of a regulation to address its implementation. Between 2012 and 2015, a process was carried out to generate this regulation that finally came into force in June 2016. This process confronted several difficulties: the involvement of multiple actors, political changes in national government, and endless negotiations to define the operational details of the regulation. The end result was one of the most discussed health policies of recent years in Chile. This article tells the story of the process defining this regulation, carried out between 2012 and 2015. It describes its evolution from a legal perspective but also reveals the trade-offs faced by the team in charge of providing the operational definitions for the implementation of the law. The article presents the main challenges as well the strategies used by the team at the Ministry of Health to overcome the many difficulties that arose during the process of implementing Chile’s food labeling and marketing law. The experience of the Chilean reform may provide practical information and lessons for other countries and policy makers embarking on the task of preventing and reducing obesity. Although the Chilean experience has its own particularities, it also suggests common difficulties for similar reform processes in terms of technical challenges—such as the definition of concepts and the scope of regulation—and political challenges—like the opposition of the food industry and conflicts of interest among governmental institutions. © 2020, © 2020 The Author(s). Published with license by Taylor & Francis Group, LLC.